The Effect of Good Governance, a Government's Internal Control System on the Performance of Bakti Kominfo Through Public Accountability as Intervening Variable - Marfiah, Yulis Widyo; Purwanto, Budi; Rumani, Daniel Dewantoro; Anggiani, Sarfilianty (Budapest International Research and Critics University, 2021)
The public sector has a primary purpose for public services and is not profit-oriented, and has flexibility in financial management. One of them is a public sector organization telecommunication and Information Accessibility Agency (BAKTI) Kominfo. BAKTI Komimfo is responsible for expanding internet access and strengthening digital infrastructure for all parts of Indonesia. This study analyzes the effect of good governance, Government Internal Control systems, and Public Accountability on the performance of BAKTI Kominfo. This study used a population of 196 BAKTI Kominfo employees using the solving method with an error rate of 5%, a sample of 140 people was obtained. The results of the study that good governance directly affect the performance of BAKTI Kominfo and also through increased accountability and SPIP affect performance through accountability.